1979
DOI: 10.1007/bf02533428
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on plasma high density lipoproteins

Abstract: The influence of vigorous activity in man on plasma lipids and lipoproteins is reviewed, with particular emphasis on high density lipoproteins. Both cross sectional and longitudinal (or training) studies have been reported, many of them of less than ideal design. Nonetheless, a consistent pattern emerges in which increased exercise levels lead to lower plasma concentrations of triglycerides and very low density lipoproteins, and of low density lipoproteins. High density lipoprotein levels increase. Sometimes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
2
2

Year Published

1982
1982
1990
1990

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(67 citation statements)
references
References 52 publications
(49 reference statements)
2
61
2
2
Order By: Relevance
“…For example, an earlier study by our group [1] and another by Adner and Castelli [2] reported significantly higher HDL-C concentrations and lower relative weights in marathon runners compared to an otherwise comparable sedentary control group. On the basis of statistically insignificant correlations between relative weight and HDL-C within exercise or control groups, both groups of investigators argued that differences in weight could not have accounted for all the observed differences in HDL-C.…”
Section: Comments Regarding Other Exercise Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, an earlier study by our group [1] and another by Adner and Castelli [2] reported significantly higher HDL-C concentrations and lower relative weights in marathon runners compared to an otherwise comparable sedentary control group. On the basis of statistically insignificant correlations between relative weight and HDL-C within exercise or control groups, both groups of investigators argued that differences in weight could not have accounted for all the observed differences in HDL-C.…”
Section: Comments Regarding Other Exercise Studiesmentioning
confidence: 76%
“…Evidence from both cross-sectional and longitudinal studies strongly suggests that running and other endurance activities increase the plasma concentration of high density lipoprotein cholesterol (HDL-C) [1][2][3][4]. Moreover, population studies indicate that lean individuals have higher HDL-C levels than those who are more obese [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the findings of Nye et al 42 who studied 17 men over the course of a 10-week training program and found that HDL 2 rose, HDL 3 fell, and consequently total HDL remained unchanged. On the other hand, many studies have found higher levels of total HDL in active as opposed to inactive subjects, 7 " 943 and in a review article on the effect of exercise on plasma HDL 44 the authors concluded that "the increase in plasma high density lipoprotein appears to be the result largely of an increase in the less dense HDL 2 subtraction." In this study, however, we found significantly higher levels of HDL 3 , but not HDL 2 , measurements in active subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lowering blood glucose (4,5) and increasing insulin sensitivity (6)(7)(8), regular exercise improves several of the recognized risk factors for cardiovascular disease. Both low-density and very-low-density lipoprotein concentrations in serum decrease with physical training (9,10), whereas high-density lipoprotein cholesterol increases (11)(12)(13)(14). Also, mild to moderate hypertension improves (15), resting pulse rate and cardiac work decrease, and physical working capacity increases with physical training.…”
mentioning
confidence: 99%